2014
DOI: 10.5942/jawwa.2014.106.0140
|View full text |Cite
|
Sign up to set email alerts
|

Naegleria fowleri: An emerging drinking water pathogen

Abstract: Naegleria fowleri (N. fowleri) is a free‐living, trophic amoeba that is nearly ubiquitous in the environment and can be present in high numbers in warm waters. It is the causative agent of primary amoebic meningoencephalitis (PAM), a rare but particularly lethal disease with a very low survival incidence. Although N. fowleri was isolated from drinking water supplies in Australia in the 1980s, it was not considered a drinking water threat in the United States until recent cases were associated with a groundwate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 90 publications
(127 reference statements)
1
37
0
Order By: Relevance
“…Given that the end response is death with a 100% percent mortality rate, it may be wise to pick a lower range of critical concentration (0.29 CFU/L) for developing standards, and the same can be applied for developing standards for other scenarios related to N. fowleri. Previous studies found the detection limit of N. fowleri to be 1-50 cells per reaction using both the nested and real-time PCR assays [19]. Considering 50 cells of N. fowleri and 200 L as a volume of water sample to be filtered, the detection limit of N. fowleri would be 0.25 N. fowleri/L which is also aligned with our calculated boundary concentration of N. fowleri using the annual risk metric.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Given that the end response is death with a 100% percent mortality rate, it may be wise to pick a lower range of critical concentration (0.29 CFU/L) for developing standards, and the same can be applied for developing standards for other scenarios related to N. fowleri. Previous studies found the detection limit of N. fowleri to be 1-50 cells per reaction using both the nested and real-time PCR assays [19]. Considering 50 cells of N. fowleri and 200 L as a volume of water sample to be filtered, the detection limit of N. fowleri would be 0.25 N. fowleri/L which is also aligned with our calculated boundary concentration of N. fowleri using the annual risk metric.…”
Section: Discussionsupporting
confidence: 87%
“…N. fowleri infections can only occur when contaminated water enters a person's body through the nose [18]. PAM has an high fatality rate, up to 98% [19,20]. Infection occurs when N. fowleri travels through the nose into the brain through the cribriform plate and begins consuming brain cells (i.e., astrocytes and neurons) [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, the interest in premise plumbing from the water industry has increased. Numerous studies have investigated different issues surrounding premise plumbing, such as corrosion [78][79][80][81] and the growth of opportunistic pathogens [82][83][84][85][86][87][88]. Premise plumbing systems are an area of the distribution system that can be overlooked by water utilities, since most premise plumbing systems are not owned or maintained by the utility and most drinking water regulations do not address premise plumbing, with the exception of the Lead and Copper Rule (LCR).…”
Section: Nitrification In Premise Plumbingmentioning
confidence: 99%
“…This free-living amoebae (FLA) has been detected in drinking water systems [26,88,90], with domestic water supply systems being implicated in a South Australian outbreak of the disease in children exposed to bathing water [91]. N. fowleri has also been detected in recreational waters [92], premise plumbing [93], irrigation systems [94] and rain water tanks in Queensland [95]. This pathogen is resistant to standard chlorine disinfection concentrations [96][97][98].…”
Section: N Fowlerimentioning
confidence: 99%